PENGARUH BUDAYA TERHADAP ISTILAH SAINS DAN TEKNOLOGI DALAM BAHASA ARAB* - Rika Astari; Syamsul Hadi; Soepomo Poedjosoedarmo; Suhandano Suhandano (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
This research aims to analyze the influence of Arabic culture to Arabic in science and technological terms in order to measure the number of words and terms owned and absorbed by Arabic language. It is a kind of descriptive qualitative study, which tends to analyze the data inductively. Both distributional method and identity method were used for analyzing the data. The result of this study shows that other findings indicate that the Arabic language terms were commonly found in mathematics science, astronomy, geography, and medical. Meanwhile, most of the terms in the fields of pharmacy, physics, chemistry and biology are absorbed into Arabic because of its universality. Moreover, many terms in information system and communication technology are widely absorbed by Arabic language in the way of translation, meaning and concept borrowing, and loan-word forms.